دور التعليم في بناء الشخصية السوية وفق المنظور القرآني - زيدان, م .د .بلسم ابراهيم (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
Personality is a term used with different meanings, some of which are common and some of them psychological, and the best meaning of it is the integrated and dynamic organization of the physical, mental, moral and social characteristics of the individual. Such as anxious and restless personalities, which were expressed as blaming or vacillating. The research has pointed to the education factor as an important factor in crystallizing the normal personality, and that any defect in this factor will inevitably lead to a defect in the construction of the personality, and that any wrong education or misconceptions in this factor will lead to the emergence of a personal that has nothing to do with its reality or society. Rather, the original meanings of its religion and its moderate spiritual values, from here the researchers elaborated on extrapolating the models that establish the normal personality in society as important factors in the renaissance of societies and the eradication of extremism and extremism and all diseases that have become intractable to treat. The research emphasized the importance of education and its necessity in building man and society and started in all of this from a Qur’an vision that reinforces the concepts and characteristics of a normal personality as a person who loves others and is keen on their benefit and warding off evil from them, at a time when God is feared and watched in its actions and whims.